Job Matching, Social Network and Word-of-Mouth Communication - Antoni Calvó-Armengol; Yves Zenou (Institute for the Study of Labor (IZA), 2003)
Workers are embedded within a network of social relationships and can communicate through word-of-mouth. They can find a job either directly or through personal contacts. From this micro scenario, we derive an aggregate matching function that has the standard properties but fails to be homogeneous of degree one because of coordination failures between workers. We show that, when the network size increases, on average, the unemployed workers hear about more vacancies through their social network but, at the same time, it is more likely that multiple vacancies reach the same unemployed worker. Above a certain critical value, this job overcrowding becomes so important that job matches decrease with network size. We then establish existence and uniqueness of the labor market equilibrium and study its properties. In dense enough networks, the equilibrium unemployment rate increases with network size whereas the latter has an ambiguous effect on wages. Finally, we demonstrate that the decentralized market equilibrium is not efficient because of both search and network externalities.
Keywords: J64; D83; 330; coordination failures; social network; personal communication; Arbeitsplatzsuchmodell; Soziales Netzwerk; Externer Effekt; Theorie; Mund-zu-Mund-Werbung